Marine Ecotourism Potential in Unggeh Island Tapanuli Tengah Regency, North Sumatra, Indonesia - Zulham Apandy Harahap; Ipanna Enggar Susetya (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
Highlight Calculated and assested the percentage of live coral coverIdentified reef fishes and calculated fish abundanceMeasured physical and chemical oceanography parameter Analyzed carrying capacity and suitability of Unggeh Island for tourism utilization especially marine diving and snorkeling.AbstractUnggeh Island located in the administration of the Village Sitardas Badiri District, Central Tapanuli Regency into a marine tourism area. The development of marine ecotourism Unggeh Island is an alternative to the economic improvement of so- ciety. This study aims to assess the potential of coral reef ecosystem in the form of percentage of life form coral, coral species and species and abundance of reef fish found in Unggeh Island waters of Central Tapanuli Regency and to analyze the suitability of coral reef ecosystem in Unggeh Island for tourism utilization es- pecially marine diving and snorkeling. Coral reef community data collection was done by using SCUBA divers equipment, in identifying The coral community used underwater photo transect (UPT) method, while coral fish diversity was observed by underwater visual census (UVC) method. Physical and chemical oceanography parameter data such as temperature, salinity, pH, current, transparency and DO are performed at each observation station. The survey results of coral reef observation at four stations showed different results. Percentage of live coral cover of station 1 to 4 were 25.40 %, 12.33%, 28.53%, and 25.53 respectively. Therefore, reef fishes found 36 species that consist of ten families and 423 individual fishes. The results showed that Unggeh Island was suitable (S2) for diving and snorkeling activities, with the carrying capacity was 3.054 persons/day.